2016
DOI: 10.1093/eurheartj/ehw018
|View full text |Cite
|
Sign up to set email alerts
|

Coronary microvascular dysfunction in chronic inflammatory rheumatoid diseases

Abstract: Chronic inflammatory rheumatoid diseases (CIRD) such as rheumatoid arthritis, systemic lupus erythematosus, and systemic sclerosis are an important risk factor for the development of ischaemic heart disease and a source of high cardiovascular morbidity and mortality. In patients affected by CIRD, inflammation can affect coronary microvascular function and contribute to the development of myocardial ischemia and cardiovascular events, even in the absence of obstructive epicardial coronary artery disease. Unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(52 citation statements)
references
References 109 publications
3
45
0
Order By: Relevance
“…While this is important for acute MI development or ischemic strokes, numerous chronic conditions are associated with microvascular dysfunction, which may be a key mechanism for heart failure development, cognitive impairment and vascular dementia 30,31 . Moreover, it has been reported that microvascular dysfunction may lead to CV events even in the absence of obstructive epicardial coronary artery disease 32 . Therefore, identification of profoundly impaired microvascular flow mediated endothelial function and abnormalities within microvessel morphology may have numerous long term clinical consequences.…”
Section: Discussionmentioning
confidence: 99%
“…While this is important for acute MI development or ischemic strokes, numerous chronic conditions are associated with microvascular dysfunction, which may be a key mechanism for heart failure development, cognitive impairment and vascular dementia 30,31 . Moreover, it has been reported that microvascular dysfunction may lead to CV events even in the absence of obstructive epicardial coronary artery disease 32 . Therefore, identification of profoundly impaired microvascular flow mediated endothelial function and abnormalities within microvessel morphology may have numerous long term clinical consequences.…”
Section: Discussionmentioning
confidence: 99%
“…(19) Cardiac positron-emission tomography (PET) has revealed impaired microvascular blood flow and reduced coronary flow reserve in SLE patients. (20)**…”
Section: Endothelial Dysfunction and Aberrant Metabolic Pathways In Slementioning
confidence: 99%
“…Stress Myocardial Perfusion Scintigraphy (MPS) is a non-invasive imaging modality used in patients with suspected CAD, commonly found in RA and SLE [68]. However, MPS has serious limitations including radiation exposure, imaging artefacts and low spatial resolution, which do not permit detection of subendocardial ischemia and small scars seen in ARD [69].…”
Section: Cardiovascular Diagnosis In the Era Of Multimodality Imagingmentioning
confidence: 99%